PENGARUH PENDEKATAN INSTRUMENTAL, DESKRIPTIF DAN STRATEGI CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN - Putri Kurnia Sari; Indira Januarti (Diponegoro Journal of Accounting, 2015)
The aim of this study is to examine the influence of corporate social responsibility on corporate financial performance. In this study the corporate social responsibility are divided into instrumental, descriptive and strategic approaches. Corporate financial performances are divided into short term and long term. The short term performance is measured by EBIT and market value, and long term performance is measured by capital expenditure and intangible assets. Dependent variables are used in this study are EBIT, market value, capital expenditure and intangible asset. Independent  variables  are  used  in  this  study  are  instrumental,  descriptive  and  strategic approaches.The populations in this study are non-financial and assurance firm listed IDX period 2011-2013. The criteria for firms are non-financial firm and assurance firm which have intangible assets. Data is collected by documentary and book study method. So the total data of this study are 108 firms. Linear regression is used to analyze data.The result showed that instrumental approach has positively significant influenced on EBIT and market value. Descriptive approach has positively significant influenced on capital expenditure and intangible asset. Strategic approach has positively significant influence on EBIT, market value, capital expenditure and intangible asset.